Improvement of Controlling in the Financial Management of Enterprises - Mazur, Nataliya; Khrystenko, Larysa; Pásztorová, Janka; Zos-Kior, Мykola; Hnatenko, Iryna; Puzyrova, Polina; Rubezhanska, Viktoriia (TEM Journal, 2021)
One of the components of a highly effective management system is operational controlling at the enterprise. At the same time, the most important indicator characterising the efficiency of the functioning of the enterprise and, accordingly, subject to controlling is its solvency, which affects the level of competitiveness of the enterprise and the efficiency of its adaptation to the changing conditions of the market environment. In this regard, the purpose of the research is to modernize the procedure of financial controlling based on the development of an integral model for determining and analysing the transformational solvency index. The article forms a universal model of financial condition assessment, in which all threshold values of the coefficients, calculated according to existing methods of financial stability assessment, are reduced to one scale and the accumulated impact of indicator values for previous periods of economic activity is taken into account.On the basis of the correlation analysis, the nature and strength of the dependence of the transformational solvency index on the factors influencing its formation and causing tendentious trends in the dynamics of its change during a certain period are determined.